Melodrama and the 'art of government': Jewish Emancipation and Elizabeth Polack's Esther, the Royal Jewess; or The Death of Haman!. Issue 2 (November 2020) - Carruthers, Jo
This article challenges historians' representations of working-class Jewish attitudes to emancipation in the early nineteenth century through a reading of Elizabeth Polack's 1835 melodrama, Esther, the Royal Jewess, or the Death of Haman! Low expectations of working-class political engagement and the working-class genre of the melodrama are challenged by the astute political content of Polack's play. Its historical and political value is revealed by placing the play within the tradition of the purimspiel, the Jewish genre that traditionally explores Jewish life under hostile government. Reading the play alongside Walter Benjamin's writings on the disparaged German melodramatic genre of the trauerspiel enables a finely articulated reading of its complex exploration of issues of sovereignty, law, and religious and political freedom.